2012
DOI: 10.1021/pr300190k
|View full text |Cite
|
Sign up to set email alerts
|

Change of Carbon Source Causes Dramatic Effects in the Phospho-Proteome of the Archaeon Sulfolobus solfataricus

Abstract: Protein phosphorylation is known to occur in Archaea. However, knowledge of phosphorylation in the third domain of life is rather scarce. Homology-based searches of archaeal genome sequences reveals the absence of two-component systems in crenarchaeal genomes but the presence of eukaryotic-like protein kinases and protein phosphatases. Here, the influence of the offered carbon source (glucose versus tryptone) on the phospho-proteome of Sulfolobus solfataricus P2 was studied by precursor acquisition independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
88
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(98 citation statements)
references
References 75 publications
(114 reference statements)
9
88
1
Order By: Relevance
“…For Sul. solfataricus, a complex phosphorylation pattern of CCM enzymes with significant changes in response to the offered carbon source was observed (439).…”
Section: Regulation At the Protein Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…For Sul. solfataricus, a complex phosphorylation pattern of CCM enzymes with significant changes in response to the offered carbon source was observed (439).…”
Section: Regulation At the Protein Levelmentioning
confidence: 99%
“…solfataricus P2 in response to different carbon sources (glucose versus tryptone) was investigated. The applied gel-and enrichment-free PAcIFIC (precursor acquisition independent from ion count) approach (438) revealed an unexpectedly large number of phosphoproteins (540 phosphoproteins) as well as a large amount of p-Tyr (54%) (439). The identified phosphoproteins are located in 21 out of 26 arCOG categories (440), indicating that most of the cellular processes are targeted by protein phosphorylation.…”
Section: Regulation At the Protein Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid triangle indicates the catalytic base of CoAindependent aldehyde dehydrogenase, and the hollow triangle indicates the phosphorylated Ser in Sso1842. 19) 100%, 99-80%, and 79-60% conserved similar residues among all sequences are shown against black, dark gray, and light gray backgrounds respectively. identified in Ttx-GAPN, but it was not conserved in the ST0064 orthologs.…”
mentioning
confidence: 99%
“…A recent proteomic study of S. solfataricus, found that Ser436 of Sso1842, an ST0064 ortholog, is phosphorylated in glucose-grown cells. 19) Ser at this position is moderately conserved among ST0064 orthologs (Fig. 1, hollow triangle), and there is a possibility that phosphorylation of this Ser was involved in the regulation of SSADH.…”
mentioning
confidence: 99%